2017
DOI: 10.5005/jp-journals-10016-1147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin C, Vitamin E, Zinc, Selenium, and Coenzyme Q10 in Infertile Men with Idiopathic Oligoasthenozoospermia

Abstract: Introduction: Accumulating evidence suggests that oxidative stress plays an important role in the development of male infertil ity and recently antioxidants have been tried to treat men with idiopathic infertility. Objective: To assess the effect of treatment with vitamin C, vitamin E, zinc, selenium, and coenzyme Q10 on seminal fluid parameters in infertile men with idiopathic oligoasthenozoo spermia. Materials and methods: A prospective randomized trial was conducted on 32 infertile men with idiopathic oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…The sperm parameters that improved were motility, sperm count, and nuclear vacuolization [ 71 ]. These findings are congruent with those of our recent study that demonstrated that daily supplementation with vitamin C (90 mg/day), vitamin E (15 mg/day), CoQ10 (4 mg/day), selenium (30 µg/day), and zinc (5 mg/day) for 3 months improved sperm concentration, progressive motility, and total motility in men with idiopathic oligoasthenozoospermia [ 72 ].…”
Section: Combination Of Oral Antioxidantssupporting
confidence: 92%
“…The sperm parameters that improved were motility, sperm count, and nuclear vacuolization [ 71 ]. These findings are congruent with those of our recent study that demonstrated that daily supplementation with vitamin C (90 mg/day), vitamin E (15 mg/day), CoQ10 (4 mg/day), selenium (30 µg/day), and zinc (5 mg/day) for 3 months improved sperm concentration, progressive motility, and total motility in men with idiopathic oligoasthenozoospermia [ 72 ].…”
Section: Combination Of Oral Antioxidantssupporting
confidence: 92%
“…A body of literature has demonstrated beneficial effects of CoQ10 and other antioxidants on semen parameters. However, there is a lack of agreement on the type and the use of individual or combination antioxidant therapy [18,30]. A recent meta-analysis also showed that doses of CoQ10 varied (200–300 mg/day) [15].…”
Section: Discussionmentioning
confidence: 99%
“…(MedCalc Software bv, Ostend, Belgium). Chi-square test was used to evaluate the association between the quality of the study and the outcomes (positive or no/negative effect) due to antioxidant treatment on semen parameters and sperm function such as oxidative stress and SDF are presented in Table 2 [ 25 26 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 …”
Section: Methodsmentioning
confidence: 99%